2015
DOI: 10.1155/2015/821094
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Clinical and Hemodynamic Consequences due to Posterior Tibial Artery Congenital Aplasia

Abstract: The exact knowledge of popliteal artery and its branches' anatomic variations is important for the clinical practice of angiology, vascular surgery, and interventional procedures. Congenital absence of the artery leads, in some cases, to early malformations of the extremity in the childhood; however, it may also remain asymptomatic. We present an unusual case of a 76-year-old male patient complaining of paraesthesia in both limbs and bilateral aplasia of posterior tibial artery (PTA). Physical examination, ank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Variations in the origin and course of the PTA and the FA have often been described after being detected either during dissection of cadaveric specimens or by arteriograms, Doppler exams, and duplex scanning of living subjects. In our analysis, we found that the PTA can be absent, hypoplastic or replaced in its distal portion or replaced altogether by the FA 1 , 4 , 6 , 19 ; it can penetrate the interosseous membrane to join the ATA; 1 it may turn anteriorly and replace the ATA; 1 it may supply all the common digital arteries 1 ; it can arise proximally to the ATA; 21 it can arise at the knee joint, above the tibial plateau; 2 , 4 , 19 , 21 it can arise from a common trunk with the ATA; 19 and it can arise directly from the popliteal artery. 4 Additionally, the FA can be hyperplasic, hypoplastic, absent or replaced by the PTA; 1 it can sometimes give rise to the ATA; 1 it can arise from the ATA; 10 it can become the peronea magna artery in cases of absence of ATA and PTA; 10 , 22 it may give origin to the dorsalis pedis artery; 2 and it may arise directly from the popliteal artery.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Variations in the origin and course of the PTA and the FA have often been described after being detected either during dissection of cadaveric specimens or by arteriograms, Doppler exams, and duplex scanning of living subjects. In our analysis, we found that the PTA can be absent, hypoplastic or replaced in its distal portion or replaced altogether by the FA 1 , 4 , 6 , 19 ; it can penetrate the interosseous membrane to join the ATA; 1 it may turn anteriorly and replace the ATA; 1 it may supply all the common digital arteries 1 ; it can arise proximally to the ATA; 21 it can arise at the knee joint, above the tibial plateau; 2 , 4 , 19 , 21 it can arise from a common trunk with the ATA; 19 and it can arise directly from the popliteal artery. 4 Additionally, the FA can be hyperplasic, hypoplastic, absent or replaced by the PTA; 1 it can sometimes give rise to the ATA; 1 it can arise from the ATA; 10 it can become the peronea magna artery in cases of absence of ATA and PTA; 10 , 22 it may give origin to the dorsalis pedis artery; 2 and it may arise directly from the popliteal artery.…”
Section: Discussionmentioning
confidence: 69%
“… 2 , 4 , 7 In the foot, if the PTA is absent, the FA gives rise to the lateral plantar artery, while the medial plantar artery is usually absent. 6 , 7 Cases have been described in the literature of idiopathic clubfoot associated with absence of the PTA. 6 There are also cases of aplasia of both the PTA and the ATA and in these cases the FA is responsible for the blood supply to the whole leg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation